Interleukin-34 produced by human fibroblast-like synovial cells in rheumatoid arthritis supports osteoclastogenesis - Hwang, Seung-Jun (BioMed Central, 2012)
INTRODUCTION: Interleukin-34 (IL-34) is a recently defined cytokine, showing a functional overlap with macrophage colony stimulating factor (M-CSF). This study was undertaken to address the expression of IL-34 in rheumatoid arthritis (RA) patients and to investigate its regulation and pathogenic role in RA. METHODS: IL-34 levels were determined in the RA synovium, synovial fluid (SF) and fibroblast-like synovial cells (FLS) by immunohistochemistry, real-time PCR, enzyme-linked immunosorbent assay and immunoblotting. RA activity was assessed using Disease Activity Score 28 (DAS28) activity in the plasma collected at baseline and one year after treatment. Conditioned media (CM) were prepared from RA FLS culture with tumor necrosis factor alpha (TNFα) for 24 hours and used for functional assay. RESULTS: IL-34 was expressed in the synovium, SF, and FLS from RA patients. The production of IL-34 in FLS was up-regulated by TNFα in RA samples compared with osteoarthritis (OA) patients. Importantly, the preferential induction of IL-34 rather than M-CSF by TNFα in RAFLS was mediated by the transcription factor nuclear factor kappa B (NF-κB) and activation of c-Jun N-terminal kinase (JNK). IL-34 elevation in plasma from RA patients was decreased after the administration of disease-modifying anti-rheumatic drugs (DMARDs) in accordance with a decrease in DAS28. CM from RAFLS cultured with TNFα promoted chemotactic migration of human peripheral blood mononuclear cells (PBMCs) and subsequent osteoclast (OC) formation, effects that were attenuated by an anti-IL-34 antibody. CONCLUSIONS: These data provide novel information about the production of IL-34 in RA FLS and indicate that IL-34 is an additional osteoclastogenic factor regulated by TNFα in RA, suggesting a discrete role of IL-34 in inflammatory RA diseases.